Comparison of sociodemographic characteristics in nursing home residents and community-dwelling elders - Yüksel, Arzu; Yilmaz, Emel Bahadir; Kesekci, Cansu Esra (Magyar Gerontológia, 2021)
Purpose: This study aimed to compare the sociodemographic characteristics in nursing home residents and community-dwelling elders.Methods: This descriptive study consisted of 342 older people between October and November 2019 (nursing home = 79, community-dwelling = 263). The data were collected by “Questionnaire Form for Individuals Living in Nursing Homes” and “Questionnaires for Individuals Living in Community-Dwelling." Comparisons between groups were made with the chi-square test. Descriptive characteristics were presented as numbers, percentage, mean, standard deviation, min. and max. scores.Results: The average age of the elderly living in a nursing home was 77.35±7.40 (min: 66, max: 97). Before coming to the nursing home, 38.0% lived with their spouses. The average age of community-dwelling older people was 70.90±5.57 (min: 65, max: 88). Of community-dwelling older people, 81.7% lived with their families. There was a significant difference between both groups regarding age, income status, having a child, having a physical disability, using dentures, ability to maintain activities of daily living, self-confidence, sleep problems, social activity, smoking rates, and history of visiting a nursing home (p < 0.05).Conclusion: Compared to the community-dwelling older people, the elderly living in a nursing home were more senior, lonely, had a lower income, had higher physical disabilities, had lower social activity and self-confidence, had more sleep problems, and smoked.